2009
DOI: 10.2147/ijgm.s5703
|View full text |Cite
|
Sign up to set email alerts
|

Primary care assessment instruments for patients at risk of, or with, persistent pain: opportunistic findings from a systematic literature review

Abstract: BackgroundEarly identification in primary care settings of individuals with, or at-risk of, developing persistent pain, is important to limit development of disability. There is little information to assist primary care providers to choose or deliver relevant, efficient, and soundly constructed assessment instruments for this purpose.ObjectiveWe recently published the findings of a literature review, which produced a compendium of assessment instruments to identify adults with, or at-risk of developing, persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…This evidence is unfortunate as primary care offers the best opportunity for early identification of patients at risk of developing chronic, persistent pain and long‐term disability [92]. Not surprisingly, models for clinical and cost‐effective pain treatment in primary care are currently lacking [93].…”
Section: Introductionmentioning
confidence: 99%
“…This evidence is unfortunate as primary care offers the best opportunity for early identification of patients at risk of developing chronic, persistent pain and long‐term disability [92]. Not surprisingly, models for clinical and cost‐effective pain treatment in primary care are currently lacking [93].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that older people are less likely to recover from chronic pain compared with younger people (Whitlock et al, 2017). Early identification of disabled individuals with persistent pain or acute pain characteristics in PHC institutions should lead to timely referrals for a more specialized health assessment and comprehensive treatment (Grimmer-Somers et al, 2009). The identification of appropriate pain management strategies and timely intervention can avoid persistent pain, as well as reduce medical and compensation costs (Blyth et al, 2004; Blyth et al, 2004; Grimmer-Somers et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of disabled individuals with persistent pain or acute pain characteristics in PHC institutions should lead to timely referrals for a more specialized health assessment and comprehensive treatment (Grimmer-Somers et al, 2009). The identification of appropriate pain management strategies and timely intervention can avoid persistent pain, as well as reduce medical and compensation costs (Blyth et al, 2004; Blyth et al, 2004; Grimmer-Somers et al, 2009). Future investigations of PHC providers’ experiences in treating patients with pain, using both non-pharmacological interventions with rational and evidence-based approaches and pharmacological interventions following the World Health Organization’s pain ladder, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisadores 18 apontam o ORTWQ como um instrumento que possui muitas vantagens como: ser de domínio público, ser multidimensional, apresentar validade e confiabilidade adequadas nas amostras em que foi utilizado e facilidade no cálculo dos escores. Além disso, esse questionário foi incluído em duas revisões sistemáticas da literatura 28,40 que fortemente recomendaram seu uso para avaliar questões ocupacionais múltiplas.…”
Section: Discussionunclassified